2019
DOI: 10.1016/j.ijcha.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for atrial fibrillation and its anticoagulant requirement in adults aged ≥40 in Jimma Town, Southwest Ethiopia: A community based cross-sectional study

Abstract: Background There is no information on the prevalence and incidence of atrial fibrillation in Ethiopia. We aimed to investigate the prevalence, risk factors and anticoagulant requirements of atrial fibrillation in an elderly Jimma population. Methods In a community-based cross-sectional study in 634 adult (≥40 years) Jimma population, we performed cardiovascular health examinations including a 12-lead electrocardiogram to estimate AF prevalence. A standardized questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
2
23
0
1
Order By: Relevance
“…This is lower than the estimates from other regions as shown by two large multinational studies conducted in 19 and 26 countries, that reported a prevalence of diabetes more than 20% in patients with AF . Obesity, another important cardiometabolic risk factor for AF, was barely reported in studies from SSA . Obesity is a growing global epidemic mostly affecting high‐income countries, but increasingly prevalent in low and middle countries including those in SSA .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…This is lower than the estimates from other regions as shown by two large multinational studies conducted in 19 and 26 countries, that reported a prevalence of diabetes more than 20% in patients with AF . Obesity, another important cardiometabolic risk factor for AF, was barely reported in studies from SSA . Obesity is a growing global epidemic mostly affecting high‐income countries, but increasingly prevalent in low and middle countries including those in SSA .…”
Section: Discussionmentioning
confidence: 61%
“…Only three studies reported the prevalence of AF in the general population in the community . This prevalence was 4.3%, 0.3%, and 0.7% in individuals aged ≥40 years, aged ≥50 years, and aged ≥70 years in Ethiopia, Ghana, and Tanzania, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations